Lung sparing and ribcage coverage in total body irradiation delivered by helical tomotherapy - Köksal, Mümtaz; Baumert, Jonathan; Schoroth, Felix; Scafa, Davide; Koch, David; Leitzen, Christina; Sarria, Gustavo R.; Giordano, Frank Anton; Chatzikonstantinou, Georgios; Schmeel, Christopher (European journal of medical research, 2022)
Helical tomotherapy (HT) is a viable method for delivering total body irradiation (TBI) when preparing patients for allogenic stem cell or bone-marrow transplantation. TBI can be planned to reduce the amount of radiation delivered to organs at risk, such as the lungs, with the aim of decreasing toxicity. However, it is important for the ribcage to receive the prescribed radiation dose in preparation for bone-marrow transplantation. In this retrospective study, we analyzed radiation dose coverage of the lungs and ribcage in patients who underwent TBI delivered by HT to achieve lung dose sparing.